STRATEGI MANAJEMEN TOKO DALAM MENINGKATKAN KINERJA PEGAWAI TOKO MA’HAD AL-ZAYTUN - Anna Risky; Sobirin; Meity Suryandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the management strategies applied in Toko Ma’had Al-Zaytun in improving employee performance. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation, then analyzed using Miles and Huberman’s interactive model. The findings reveal that management strategies were implemented through three main stages: planning, implementation, and evaluation. Planning involved structured work distribution and a shift system; implementation emphasized discipline, sincerity, and responsibility based on Islamic values; while evaluation was carried out through direct supervision and regular performance assessment. Supporting factors include transformational leadership, open communication, and a conducive work environment, whereas inhibiting factors are limited human resources, inadequate facilities, and lack of training. This study contributes theoretically by integrating modern strategic management theory with Islamic values, practically by providing recommendations for managing pesantren business units, and methodologically by proving the relevance of qualitative descriptive approaches in exploring complex managerial phenomena.